Immunohistochemistry and in situ hybridization of human carcinomas - Hayat, M. A., 1940- (Elsevier Academic Press, 2004)
Classical histology has been augmented by immunohistochemistry (the use of specific antibodies to stain particular molecular species in situ). Immunohistochemistry has allowed the identification of many more cell types than could be visualized by classical histology, particularly in the immune system and among the scattered hormone-secreting cells of the endocrine system. This book discusses all aspects of immunohistochemistry and in situ hybridization technologies and the important role they play in reaching a cancer diagnosis. It provides step-by-step instructions on the methods of additional molecular technologies such as DNA microarrays, and microdissection, along with the benefits and limitations of each method. * The only book available that translates molecular genetics into cancer diagnosis * Methods were developed by internationally-recognized experts and presented in step-by-step manner * Results of each Immunohistochemical and in situ hybridization are presented in the form of color illustrations.